2019
DOI: 10.3390/w11051021
|View full text |Cite
|
Sign up to set email alerts
|

Capture and Release of Phosphorus by Periphyton in Closed Water Systems Influenced by Illumination and Temperature

Abstract: Periphyton is known to play an important role in the self-purification of aquatic ecosystems. However, little attention has been paid to the understanding of P distribution and its partitioning influenced by the physical parameters when periphyton is separated from the sediment. In this work, the effect of periphyton on the capture and release of phosphorus in closed water systems was studied and the influence of illumination and temperature conditions were investigated. Results showed that phosphorus was tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
(32 reference statements)
0
2
0
1
Order By: Relevance
“…Talvez se o experimento tivesse sido continuado, os tanques com sedimento poderiam ter se mantido produtivos. Como sugestões para futuros trabalhos recomenda-se monitorar o sistema por maior período, bem como avaliar a produção de perifíton sobre o sedimento (epipelon), que tem sido apontado como importante fator na manutenção das baixas concentrações de fósforo na água (CANO; CASCO;CLAPS, 2016;ZHAO et al, 2019;YI et al, 2019) e monitorar os índices de oxigênio dissolvido, visto que os índices de oxigenação nos tanques podem ser responsáveis pela retenção do fósforo no sedimento ou sua liberação para a coluna d'água, conforme reportado em estudos recentes (HORPILLA, 2019;LIU et al, 2020).…”
Section: Methodsunclassified
“…Talvez se o experimento tivesse sido continuado, os tanques com sedimento poderiam ter se mantido produtivos. Como sugestões para futuros trabalhos recomenda-se monitorar o sistema por maior período, bem como avaliar a produção de perifíton sobre o sedimento (epipelon), que tem sido apontado como importante fator na manutenção das baixas concentrações de fósforo na água (CANO; CASCO;CLAPS, 2016;ZHAO et al, 2019;YI et al, 2019) e monitorar os índices de oxigênio dissolvido, visto que os índices de oxigenação nos tanques podem ser responsáveis pela retenção do fósforo no sedimento ou sua liberação para a coluna d'água, conforme reportado em estudos recentes (HORPILLA, 2019;LIU et al, 2020).…”
Section: Methodsunclassified
“…The macrophyte, Potamogeton crispus L., enhanced the richness of epiphytic algae by reducing excess nutrient concentrations and enhancing water transparency (Lv, He, Hong, Liu, & Yu, 2019). Periphyton captured more P when illuminated at 70 than 20 µmol photons m −2 s −1 at 25°C and 35°C, but not at 15°C (Zhao, Chen, Xiong, & Wu, 2019).…”
Section: Algaementioning
confidence: 99%
“…Liu, Sun, et al (2019) found algal diversity, bacterial diversity, and EPS content in paddy fields were positively correlated with biomass P content (concurrent with an increase in green algal abundance) and negatively correlated with water total P concentration, which means microbiota play a role in P immobilization from the sediment and P uptake from the water column. Zhao, Chen, et al (2019) observed that in closed water systems, periphyton temporarily stored P following nutrient input and temperature and light strongly influenced the capture and release of P. Salinization in a mesocosm experiment led to an increase in biomass of phytoplankton, which McGowan, Leavitt, Barker, and Moss (2020) related to increased P release while aquatic plants and periphyton declined in the benthos. Benthic diatoms, such as Nitzschia Hass., may be used to manage the rate of N and P released from the sediment to reduce nutrient pollution from aquaculture (Xing et al, 2019).…”
Section: Algaementioning
confidence: 99%